The effects of ketogenic and chitosan-based diets on submandibular salivary gland in rat model: a comparative histological study - Mahmoud Mohamed Aboulfotoh (BMC, 2024)
Abstract Objective This study was carried out in the submandibular salivary glands (SSGs) of rats to demonstrate the effect of a ketogenic diet (KD) in comparison with dietary chitosan supplementation. Method Eighteen albino rats were randomly divided into three equal groups of six animals each. Rats in Group I were fed a balanced diet and considered controls. Meanwhile, those of Groups II and III were fed a KD, a balanced diet with high molecular weight chitosan, respectively. After 45 days, rats were euthanized, and the SSGs were dissected carefully for staining with hematoxylin and eosin (H&E), alpha-smooth muscle actin (α-SMA) immunohistochemical staining, and Congo red special stain. Quantitative data from α-SMA staining and Congo red staining were statistically analyzed using one-way ANOVA followed by Tukey's multiple comparisons post hoc test. Results Regarding Congo red and α-SMA staining, one-way ANOVA revealed a significant difference between the three groups. For α-SMA staining and Congo red staining, Group II had the highest mean values of 91.41 ± 3.30 and 68.10 ± 5.04, respectively, while Group I had the lowest values of 56.13 ± 3.96 and 16.87 ± 2.19, respectively. Group III had mean values of 60.70 ± 3.55 for α-SMA and 19.50 ± 1.78 for Congo red. Tukey's multiple comparisons post hoc test revealed significant differences between groups I & II and between groups II & III (P < 0.05). Meanwhile, there was a nonsignificant difference between groups I and III (P > 0.05). Conclusion A KD has a deleterious effect on rats' SSG whatever the test we used, and dietary chitosan supplementation ameliorates these damaging effects.